Pobreza subjetiva desde el enfoque del ingreso en la parroquia Zumbahua del cantón Pujilí, provincia de Cotopaxi - Rubio Guanotuña, Elisa Jazmín (2024)
ABSTRACT: The objective of this study is to analyze subjective poverty in “Zumbahua” parish, Pujilí canton, using an income-based approach. A questionnaire was created based on research studies and distributed to 197 residents from various communities. For this purpose, a discrete choice logit model was applied, demonstrating a high level of confidence. Additionally, a descriptive analysis of the survey results is conducted, revealing that most respondents are male, over 30 years old, and mention that their monthly income is not enough for their desired purposes. The main results of the econometric model show that characteristics such as education level, age, marital status, area of residence, number of children, and occupation have a significant effect on the probability of whether income is sufficient to cover the expenses presented during the month, indicating that these characteristics are highly relevant for self-perceived poverty.